2017
DOI: 10.5812/traumamon.15845
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Common Medical Errors in a Children’s Hospital NICU Using Failure Mode and Effects Analysis (EMEA)

Abstract: Background: Neonatal intensive care units are prone to a variety of errors due to their special conditions. Failure mode and effects analysis (FMEA) is a method for risk assessment and management, which assesses the safety of patient care processes through its system approach. Objectives: The present study aimed to identify and assess common medical errors at Amirkola Children's hospital NICU in 2016. Methods: This was a cross-sectional study conducted from September 2015 to February 2016 in the NICU of Amirko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Some other studies 13 39–43 had used mixed scales adopted from literature. One study had used the scale introduced by the ISMP, Canada, 44 which is also a mix of a 4-point scale and a 5-point scale.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some other studies 13 39–43 had used mixed scales adopted from literature. One study had used the scale introduced by the ISMP, Canada, 44 which is also a mix of a 4-point scale and a 5-point scale.…”
Section: Resultsmentioning
confidence: 99%
“…We found that FMEA is a valuable prospective analytical method that can be applied to most of the processes in healthcare. According to our study, FMEA can be successfully applied to evaluate the safety of existing procedures, 13 24 26 27 16-22 30–33 35 36 39–42 44–46 process changes 43 and assess the implementation of new policies. 29 Furthermore, we encountered studies which employed FMEA to evaluate the impact of different situations such as drug shortages 25 and to select the best choice over two alternatives.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations